Reproductive concerns and associated factors among female chronic kidney diseases patients: a Multi‐Center Cross‐Sectional Study. Issue 5 (10th March 2021) - Wang, Fang; Ma, Dengyan; Salerno, Stephen; Chen, Yi; Liu, Min; Luo, Yan; Diao, Yongshu; Chen, Chongcheng; Fu, Ping; Li, Yi
Abstract: Aim: The study aimed to investigate the current status of reproductive concerns and explore the associated factors among young female chronic kidney disease (CKD) patients. Design: A multi‐center cross‐sectional study was designed. Methods: The study was conducted in six representative tertiary hospitals across southwest China. A total of 295 female Chronic kidney disease patients between 18–45 years of age completed a 20 min, web‐based survey, which included demographics and disease‐related information questionnaire, Reproductive Concerns Scale, Generalized Anxiety Disorder 7 (GAD‐7) instrument and Patient Health Questionnaire 9 (PHQ‐9) instrument. Result: The survey total collected 270 valid questionnaires. The mean reproductive concern score was 54.39 ± 10.90 (out of a maximum of 90), with the mean scores for sub‐scales ranging from 7.80 ± 1.69 to 10.44 ± 1.85. Multiple regression analysis showed that those with higher reproductive concerns were more likely to have pregnancy intentions, to be in Chronic kidney disease stages 1–3, and to have a higher GAD‐7 score. This study offered further evidence of the need for improved education and emotional support surrounding reproductive concerns among young Chinese women with Chronic kidney disease.